2000
DOI: 10.1016/s0735-1097(00)00730-0
|View full text |Cite
|
Sign up to set email alerts
|

Sarcolemmal Na+/H+ exchanger activity and expression in human ventricular myocardium

Abstract: Sarcolemmal NHE activity of human ventricular myocytes arises from the NHE1 isoform and is inhibited by HOE-642. Sarcolemmal NHE activity is significantly greater in recipient hearts with chronic end-stage heart failure than it is in unused donor hearts, and this difference is likely to arise from altered posttranslational regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(76 citation statements)
references
References 41 publications
4
70
1
Order By: Relevance
“…However, the cardiovascular and cGMP responses to these hormones are markedly attenuated, indicating impaired receptor or postreceptor responsiveness of GC-A. 1,5 Our present findings in GC-A-deficient mice indicate that an inhibition of cardiac ANP/GC-A signaling might contribute to the increased activity of myocardial NHE-1 that has been observed in these patients 21 and thereby to the progression of cardiac remodeling and dysfunction.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, the cardiovascular and cGMP responses to these hormones are markedly attenuated, indicating impaired receptor or postreceptor responsiveness of GC-A. 1,5 Our present findings in GC-A-deficient mice indicate that an inhibition of cardiac ANP/GC-A signaling might contribute to the increased activity of myocardial NHE-1 that has been observed in these patients 21 and thereby to the progression of cardiac remodeling and dysfunction.…”
Section: Discussionmentioning
confidence: 60%
“…14,18,22 In some studies, increased cardiac protein expression levels of NHE-1 appear to be involved in the subsequent pathological changes. 8 In other studies, and in particular, in human heart failure, enhanced NHE-1 activity is not correlated with an increase in expression, 21,22 suggesting a role for posttranslational mechanisms. In accordance with the latter, in GC-A Ϫ/Ϫ mice the cardiac NHE-1 expression levels were not altered.…”
Section: Enhanced Nhe-1 Activity Leads To Increased Intracellular Camentioning
confidence: 84%
“…In this regard, Iso-induced CH seems to differ from other models of CH in which enhanced NHE-1 activity 17,18 is not correlated with an increase in expression of the antiporter, 17,19 suggesting a role for posttranslational mechanisms. Iso-induced effects are attenuated by chronic inhibition of the exchanger.…”
Section: Discussionmentioning
confidence: 65%
“…2 In addition, comparable myocardial protective actions have been reported in settings of regional and global myocardial ischemia in nonfibrillating hearts from different species. 17,18 Sarcolemmal NHE-1 is expressed in human myocardium, 25 and clinical trials have demonstrated myocardial benefits derived from NHE-1 inhibition in subsets of patients undergoing emergent coronary revascularization. 26 Thus, effects similar to those reported here in pigs may also apply to humans and facilitate closed-chest resuscitation from VF.…”
Section: Discussionmentioning
confidence: 99%